Antiviral effects of amantadine and iminosugar derivatives against hepatitis C virus. - Steinmann, E; Whitfield, T; Kallis, S; Dwek, R; Zitzmann, N; Pietschmann, T; Bartenschlager, R (2007)
UNLABELLED: Current therapy of chronic hepatitis C is based on the combination of pegylated interferon-alpha and ribavirin. In spite of 50% sustained virological response, therapy is still limited by unsatisfying success rates with genotype 1 infections and adverse side effects. One attempt to increase success rates is triple combination therapy of interferon and ribavirin with amantadine, a drug assumed to interfere with HCV p7 ion channel function. However, results from clinical trials indicate limited efficacy and the antiviral activity is unclear. In contrast, NS3 protease inhibitors have shown potent antiviral effects in clinical trials but rapid selection for drug resistance may limit their benefit. Targeting cellular factors required for HCV is therefore an attractive alternative. In this study, employing a system for production of infectious HCV particles in cell culture, we determined the antiviral effects of amantadine and iminosugar derivatives; the second of which primarily target host cell glucosidases required for folding and maturation of HCV envelope glycoproteins. We found that across a spectrum of HCV isolates and genotypes, amantadine affected neither RNA replication nor the release or infectivity of HCV particles. In agreement, p7 ion channel activity was not affected by amantadine, demonstrating that amantadine is not an HCV-selective antiviral. In contrast, a dose-dependent reduction of virus titers was achieved with iminosugars. Furthermore, HCV was rapidly eliminated from cell culture upon passage in the presence of a long alkyl chain deoxynojirimycin (DNJ). CONCLUSION: Iminosugar derivatives are potential drugs for treatment of HCV infections.